Numerical simulation study on the smoke spread process under the influence of the hollow floorboard in the logistics warehouse. (November 2019) - Tao, Shifan; Dong, Xuan; Tan, Yaxin; Wei, Yansong; Wang, Bowen; Huang, Yufeng
Abstract: In this paper, the fire hazard of logistics warehouses under the influence of the mezzanine shelves structure is studied. The relationship between the hollowing rate of the mezzanine shelves board and the fire smoke diffuse spread is evaluated, with the hollowing rates of 5%, 10%, 15%, 20%, 25%, 30% and 50% are mentioned. The obscuration rate, HRR (heat release rate) and T alarm (time of fire alarm) are obtained through FDS (Fire Dynamics Simulator) simulation study, and some valuable results are yield. The result shows that the lower level of hollowing rate, the greater variation of the obscuration rate value along with distance. Furthermore, the relationship between T alarm and hollowing rate was fitted by the functional relationship Y = a / ( a + b x + c x 2 ) . Except for smoke detector above the fire source R = 0.69, the fitting results of other positions are better, and R values are all above 0.97. The research provides basic theoretical for the selecting and setting of fire alarm system in the warehouse, and the analysis and evaluation of warehouse fire risk which have decent practical significance and application value.